Faktor-faktor yang berhubungan dengan kejadian diare pada balita - Bella Tania Putri; Suwito Suwito; Dina Dwi Nuryani (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Globally, there are around 1.7 billion cases of diarrhea in children each year, and diarrhea is the main cause of malnutrition in children under five. In developing countries, diarrhea causes 1.8 million deaths of children under five, which has increased from 1.5 million in the last 20 years. The causes of diarrhea are related to host, agent, and environmental factors. In Indonesia, diarrhea remains a serious public health problem, especially among toddlers. Purpose: to analyze the factors related to diarrhea among toddlers in the working area of the Labuhan Ratu Health Center in 2024. Method: This research used a quantitative analytic method with a cross-sectional design. The population was all toddlers in the working area of the Labuhan Ratu Health Center, totaling 4,589 children. A sample of 188 toddlers was selected using a simple random sampling technique. Primary data were collected using questionnaires. The data were analyzed using univariate, bivariate (Chi-square test), and multivariate (logistic regression). Results: The study showed that nutritional status (p = 0.011; OR = 2.369), maternal education (p = 0.018; OR = 2.395), exclusive breastfeeding (p = 0.006; OR = 2.394), handwashing habits (p = 0.000; OR = 5.425), and source of drinking water (p = 0.004; OR = 2.630) had significant relationships with diarrhea in toddlers. Economic level (p = 0.075) and immunization history (p = 0.200) were not significantly related. The most dominant factor was handwashing habits (p = 0.000; OR = 4.772). Conclusion: There is a significant relationship between several factors and diarrhea incidence in toddlers, especially handwashing behavior. It is recommended that the health center increase education for pregnant women and mothers of toddlers on the importance of handwashing, exclusive breastfeeding, balanced nutrition, and clean water to prevent diarrhea.